Vismodegib in PAMAM-dendrimers for potential theragnosis in skin cancer - David E. Ybarra; Maria Natalia Calienni; Luis Felipe Barraza Ramirez; E. Tais Aguayo Frias; Cristian Lillo; Silvia del Valle Alonso; Jorge Montanari; Fernando C. Alvira (Elsevier, 2022)
Vismodegib (VDG) is an antineoplastic, a first-in-class Hedgehog signaling pathway inhibitor, indicated to treat locally advanced or metastatic basal cell carcinoma. Treatment with this drug was approved in 2012 by the US-FDA for oral administration (dose of 150 mg per day) in patients with a refusal of radiotherapy or surgery. However, it presents side effects that influence patient adherence to treatment. Polyamidoamine (PAMAM) dendrimers (D) are promising drug-delivery systems with high water solubility. Additionally, they can penetrate the skin barrier. In this work, we used amine-terminated (DG4.0) and carboxy-terminated (DG4.5) dendrimers of generation 4.0 and 4.5, respectively. We demonstrated that the complexation of VDG with dendrimers (D:VDG complexes) increased its concentration in the aqueous medium. We carried out characterization studies of the complexes to understand how dendrimers interact with VDG, and we found the optimal molar ratios of complexation.Furthermore, as these dendrimers have shown non-traditional fluorescence, we studied the effect on the emission patterns of the D:VDG complexes. This feature allowed for fluorescence monitoring of skin penetration of the complexes, while RP-HPLC quantified VDG. Although the complexes managed to penetrate human skin explants, DG4.0:VDG presented a better penetration profile. The concentration of VDG complexed with dendrimers in the viable epidermis and dermis was 1.95 µg/ml and 5.47 µg/ml for DG4.0 and DG4.5, respectively. These results show the theragnostic potential of these formulations in treating basal cell carcinoma.